Mechanical Strength and Hydrophobicity of Cotton Fabric after SF6 Plasma Treatment - Kamlangkla, K. (2010)
Surface treatments to tailor fabric properties are in high demand by the modern garment industry. We studied the effect of radio-frequency inductively coupled SF 6 plasma on the surface characteristics of cotton fabric. The duration of the treatment and the SF 6 pressure were varied systematically. We measured the hydrophobicity of treated cotton as a function of storage time and washing cycles. We used the weight loss (%) along with the etching rate, the tensile strength, the morphology changes and the hydrophobicity of the fabric as observables after treatments with different plasma conditions. The weight loss remains below 1% but it significantly increases when the treatment time is longer than 5 min. Substantial changes in the surface morphology of the fiber are concomitant with the increased etching rate and increased weight loss with measurable consequences in their mechanical characteristics. The measured water absorption time reaches the maximum of 210 min when the SF 6 pressure is higher than 0.3 Torr. The water contact angle (149 °) and the absorption time (210 min) of cotton treated with extreme conditions appear to be durable as long as the fabric is not washed. X-ray photoelectron spectroscopy analysis reveals that the water absorption time of the fabric follows the same increasing trend as the fluorine/carbon ratio at the fabric surface and atom density of fluorine measured by Ar actinometer.